2014
DOI: 10.1186/1745-6215-15-469
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib versus placebo as adjuvant therapy after chemoradiation in a double-blind, phase III study (LUX-Head & Neck 2) in patients with primary unresected, clinically intermediate-to-high-risk head and neck cancer: study protocol for a randomized controlled trial

Abstract: BackgroundOver 50% of patients with head and neck squamous cell carcinoma (HNSCC) present with locoregionally advanced disease. Those at intermediate-to-high risk of recurrence after definitive therapy exhibit advanced disease based on tumour size or lymph node involvement, non-oropharynx primary sites, human papillomavirus (HPV)-negative oropharyngeal cancer, or HPV-positive oropharynx cancer with smoking history (>10-pack-years). Non-surgical approaches include concurrent chemoradiotherapy, induction chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The 5-year survival rate of cervical cancer is ~20-30% (2). The major cause of the low survival rates may be due to high recurrence rates of 80%, poor progression and tolerance to chemotherapy (3). As a first-line agent, paclitaxel serves an important role in the treatment of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate of cervical cancer is ~20-30% (2). The major cause of the low survival rates may be due to high recurrence rates of 80%, poor progression and tolerance to chemotherapy (3). As a first-line agent, paclitaxel serves an important role in the treatment of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Progression-free survival was 2.6 months for the afatinib arm and 1.7 months for the methotrexate arm (p=0.030; hazard ratio 0.80) (35). Separate phase III trials in HNSCC are ongoing to assess the efficacy of single-agent afatinib or lapatinb in the adjuvant setting to reduce the risk of disease recurrence and progression (36). Even though there is evidence that afatinib has activity in the recurrent/metastatic HNSCC setting, the clinical benefit with this molecularly-targeted agent is quite modest suggesting that the kinase-independent actions of EGFR may be able to compensate for kinase activity blockade and thus, a select population of HNSCC cells may utilize a non-canonical EGFR pathway to maintain survival.…”
Section: Discussionmentioning
confidence: 99%
“…The phase II trial indicated a comparable clinical efficacy of afatynib to cetuximab in recurrent HNSCC treated previously with chemotherapy based on platinum (47). It is evaluated in the phase III trial as an adjuvant following chemoradiotherapy in the treatment of unresectable advanced (stages III to IVa) HNSCC (48). One of the phase II trials determined that dacomitynib, another EGFR inhibitor, indicated clinical activity in the first-line treatment of recurrent or metastatic HNSCC (49).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%